Taxation of e-commerce: Determination of permanent establishment in Malaysia - Othman, Zaleha; Mohd Hanefah, Hajah Mustapha; Bidin, Zainol (Universiti Utara Malaysia, 2004)
Permanent establishment in taxation has been in existence since the 18th century. Originated from the Prussian time in 1845 the concept of permanent establishment has been used to refer as space the conduct of business activity, which means permanence and location within an area rather than the physical location in one specific area. Progressively, the definition of permanent establishment has been improved through the years to include real center of management, mining and oiled fields, factories, workshop, agencies, warehouse, office and deports. At present Permanent establishment has been recognized by OECD as the fixed place of business, which the business of an enterprise is wholly or partly is carried on. Permanent establishment is a long established international tax concept used as an innovator to legal authority to tax transactions. Nonetheless, the concept of PE (which is the demarcation point of fixed place of business) has been triggered by e-commerce. This is so because the border less nature of e-commerce has created difficulty of identifying the sources of income which has trigger the presence concept of a business. Consequently, many countries have raised concern over the practicality of the current tax systems in taxing e-commerce. Much has been said about the importance of reviewing the tax system to suit transactions of e-commerce but sparse study has been conducted in this particular area.